Glaciers, Permafrost and Lake Levels at the Tsengel Khairkhan Massif, Mongolian Altai, During the Late Pleistocene and Holocene - Michael Walther; Avirmed Dashtseren; Ulrich Kamp; Khurelbaatar Temujin; Franz Meixner; Caleb G. Pan; Yadamsuren Gansukh (Geosciences, 2017)
Understanding paleo—and recent environmental changes and the dynamics of individual drivers of water availability is essential for water resources management in the Mongolian Altai. Here, we follow a holistic approach to uncover changes in glaciers, permafrost, lake levels and climate at the Tsengel Khairkhan massif. Our general approach to describe glacier and lake level changes is to combine traditional geomorphological field mapping with bathymetric measurements, satellite imagery interpretation, and GIS analyses. We also analysed climate data from two nearby stations, and measured permafrost temperature conditions at five boreholes located at different elevations. We identified four glacial moraine systems (M4-M1) and attribute them to the period from the penultimate glaciation (MIS 4/5) until the Little Ice Age (MIS 1). During the Local Last Glacial Maximum (LLGM; MIS 2), a glacier reached down into the western Kharganat Valley and blocked it, resulting in the formation of the endorheic Khar Lake basin. Subsequently, the lake was fed mainly by precipitation and permafrost meltwater. In recent years, glaciers have been in strong recession, yet Khar Lake levels have remained relatively stable, which is in contrast to mainly decreasing lake levels in other regions throughout Mongolia. While temperatures in the Altai are increasing (leading to increasing evaporation), precipitation in higher elevations has increased, which—in addition to increased glacier and permafrost melting—would counteract the increasing aridity effects. A systematic and holistic monitoring of glaciers, permafrost, lake levels and climate in the Mongolian Altai is necessary, and results from (sub-)disciplines need to be correlated.